The Zoo at the Edge of the World - Gale, Eric Kahn, 1986-; Nielson, Sam (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2014)
"Marlin, a stutterer, can talk smoothly and freely with the jungle animals that populate his father's zoo in South America--until a mysterious man-eating black jaguar that his father catches and brings back home talks back"--
Ages 8-12.
Keywords: Human-animal communication -- Fiction; Jungle animals -- Fiction; Zoos -- Fiction; Stuttering -- Fiction; Human-animal communication -- Juvenile fiction; Jungle animals -- Juvenile fiction; Zoos -- Juvenile fiction; Stuttering -- Juvenile fiction; Abused children -- Juvenile fiction; Imperialism -- 19th century -- Juvenile fiction; Guyana -- Juvenile fiction; Abused children; Human-animal communication; Imperialism; Jungle animals; Stuttering; Zoos; Guyana; 1800 - 1899; Fiction; Juvenile works